PERILAKU PENCEGAHAN PENYAKIT TERHADAP KEJADIAN SKABIES PADA SANTRI DI PONDOK PESANTREN AL-FALAH PUTERA BANJARBARU - Musafaah; Kustantie, Anna Maulina; Rachmawati, Kurnia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Scabies is a contagious skin disease caused by infestations of Sarcoptes scabies. Healthpromotion behavior including of disease prevention behaviors which means avoiding diseasetransmission. The objective of this study was to determine the relationships between diseaseprevention behaviors and scabies incidence on students at saAl-Falah Putera’s boarding schoolBanjarbaru. The methods of this study was a retrospective study (case control study), toward theboarding students at the boarding school Al-Falah Putera’s Banjarbabaru. Respondents weredivided into 2 groups: the case group (n = 36) and control group (n = 36). The instrument usedin the form of a questionnaire the behavior of scabies disease prevention. The result of this studyshowed that behavioral scabies prevention of disease by not exchanging clothes and prayer toolsin both categories as many as 52 students (72.2%), not alternating towels in both categories areas many as 59 students (81.9%), and maintain the cleanliness of the beds in both categories asmany as 52 students (72.2%). The Results of Chi Square test related to scabies disease preventionbehaviors by not exchanging clothes and tools prayer, not alternating towel and maintain thecleanliness of the bed showed p= 0.792, p= 1.000, p= 0.066 respectively.